Structure and Dynamics of the Gut Bacterial Community Across the Developmental Stages of the Coffee Berry Borer, Hypothenemus hampei - Mejía-Alvarado, Fernan Santiago; Ghneim-Herrera, Thaura; Góngora, Carmenza E.; Benavides, Pablo; Navarro-Escalante, Lucio (Frontiers in Microbiology, 2021)
The coffee berry borer (CBB); Hypothenemus hampei (Coleoptera: Curculionidae), is widely recognized as the major insect pest of coffee crops. Like many other arthropods, CBB harbors numerous bacteria species that may have important physiological roles in host nutrition, detoxification, immunity and protection. To date, the structure and dynamics of the gut-associated bacterial community across the CBB life cycle is not yet well understood. A better understanding of the complex relationship between CBB and its bacterial companions may provide new opportunities for insect control. In the current investigation, we analyzed the diversity and abundance of gut microbiota across the CBB developmental stages under field conditions by using high-throughput Illumina sequencing of the 16S ribosomal RNA gene. Overall, 15 bacterial phyla, 38 classes, 61 orders, 101 families and 177 genera were identified across all life stages, including egg, larva 1, larva 2, pupa, and adults (female and male). Proteobacteria and Firmicutes phyla dominated the microbiota along the entire insect life cycle. Among the 177 genera, the 10 most abundant were members of Ochrobactrum (15.1%), Pantoea (6.6%), Erwinia (5.7%), Lactobacillus (4.3%), Acinetobacter (3.4%), Stenotrophomonas (3.1%), Akkermansia (3.0%), Agrobacterium (2.9%), Curtobacterium (2.7%), and Clostridium (2.7%). We found that the overall bacterial composition is diverse, variable within each life stage and appears to vary across development. About 20% of the identified OTUs were shared across all life stages, from which 28 OTUs were consistently found in all life stage replicates. Among these OTUs there are members of genera Pantoea, Erwinia, Agrobacterium, Ochrobactrum, Pseudomonas, Acinetobacter, Brachybacterium, Sphingomonas and Methylobacterium, which can be considered as the gut-associated core microbiota of H. hampei. Our findings bring additional data to enrich the understanding of gut microbiota in CBB and its possible use for development of insect control strategies.